2022
DOI: 10.1111/acel.13661
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the S1 neuronal calcium network to insulin and Bay‐K 8644 in vivo: Relationship to gait, motivation, and aging processes

Abstract: Neuronal hippocampal Ca2+ dysregulation is a critical component of cognitive decline in brain aging and Alzheimer's disease and is suggested to impact communication and excitability through the activation of a larger after hyperpolarization. However, few studies have tested for the presence of Ca2+ dysregulation in vivo, how it manifests, and whether it impacts network function across hundreds of neurons. Here, we tested for neuronal Ca2+ network dysregulation in vivo in the primary somatosensory cortex (S1) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 70 publications
0
13
1
1
Order By: Relevance
“…Signal processing and data extraction were accomplished using a custom MATLAB pipeline as previously described (Lin et al, 2022).…”
Section: P Image Processing and Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal processing and data extraction were accomplished using a custom MATLAB pipeline as previously described (Lin et al, 2022).…”
Section: P Image Processing and Extractionmentioning
confidence: 99%
“…Our lab has previously described alterations in gait performance with aging that reflect on dysregulation in neuronal networks using the F344 rat model of aging, where number of active neurons and connectivity were increased with aging (Lin et al, 2022) synchronicity were noted in the anesthetized F344 rat. This is likely because the use of anesthesia has been shown to increase neuronal synchrony (Goltstein et al, 2015), possibly influencing our ability to detect age-related effects in the anesthetized rat (i.e., ceiling effect).…”
Section: Gait Behavior Testingmentioning
confidence: 99%
“…In the same animals, INI was also able to decrease the time taken to ambulate down a corridor during a gait behavioral task [ 137 ] perhaps indicating that the changes in ambulation were reflected by alterations in network communication. Further, in this same model, we also found that INI was able to significantly alter measures of CBF ( Figure 4 ).…”
Section: Insulin Sensitivity In the Brain: Contradictory Evidencementioning
confidence: 99%
“…Cent symbols (¢) denote Bonferroni post hoc significance ( p < 0.05) between INS and INI at the timepoints indicated. Figure reproduced from Lin et al, 2022 [ 137 ].…”
Section: Figurementioning
confidence: 99%
“…12 Frazier menyatakan bahwa, ada bukti yang berkembang tentang peran tujuan agama dalam fungsi manusia yang positif serta kesejahteraan subjektif. 13 Jung berpendapat bahwa agama memiliki dampak positif dan dia secara khusus mendorong praktik keagamaan tersebut. 14…”
Section: Pembahasanunclassified